PELATIHAN E-LEARNING DASAR BAGI GURU-GURU BIDANG STUDI IPS SE KOTA KEFAMENANU - Darsono Nababan; Yasinta Rema (STKIP Citra Bakti, 2021)
The COVID-19 emergency period changed the education system in Indonesia in a very short time, requiring every student to study remotely. Of course this encourages teachers to innovate and policy makers in this case the Ministry of Education and Culture of the Republic of Indonesia to make adjustments during the COVID-19 pandemic by changing some rules by issuing circular letter number 2 of 2020 regarding the prevention and handling of COVID-19 in the environment. Ministry of Education and Culture, as well as circular letter number 3 of 2020 regarding the prevention of COVID-19 in education units. The readiness of schools in implementing distance learning received various positive and negative responses from various elements of society. The readiness of teachers in the implementation of online education has not been maximized, this is due to the lack of knowledge in the field of Information Technology. Therefore, to support government policies in implementing distance learning and minimizing the spread of the COVID-19 virus, teachers need to be equipped with e-learning implementation. Teachers are expected to be able to compile learning materials using online e-learning using the Edmodo platform so that teachers are not only fixated on one learning model using conventional models